PENERAPAN PEMBELAJARAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN 8 DURI BARAT KECAMATAN MANDAU KABUPATEN BENGKALIS - Masriana Masriana; Zariul Antosa; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
ematic class III SDN 8 Duri Barat From 20 student who achieve KKM just 8 student (40%) while student who did’nt complete 12 student (60 %) with an average of 64.This aims of study to matcase study result mathematic school years 2015-2016. This research subjet student class III SDN 8 Duri Barat Kecamatan Mandau kabupaten Bengkalis amount of 20 students research is the action research class with the two cycle. This case can prove with the actiuty teacher score after leaning increase with the model PMRI increase experience from first cycle appointment first teacher activity get 65 score with the enough score and increase to 5 poin to 70 on the second appointment with the good category and than second cycle on the first appointment increase amount of 15 poin with the 85 score with the excellent category and the four appointment increase again to 5 poin with amount of 90 excellent category. Student activity can applied learning with the model PMRI increase from one cycle an the first appointment students activityvcan reach 65 score with enough category and arrow to 5 poin to 70on the second appointment with category. And than second cycle first appointment increased amount of 10 poin with the 80 score with excellent category and the four appointment increased again amount of 5 poin with the all score 85 excellent category. The learning outcomes after applied learning model PMRI increased from basic score with 1179 avarage 59,75 increased on the first cycle to 1570 with the average 78,5 and on the II cycle increased to 1880 with the average 94. Therefore can concluded that hypothesis the research can be applied on learning PMRI can increased studt result mouth student class III SDN 8 Duri Barat.Keywords : PMRI, Learning Outcomes Mathematics